1997
DOI: 10.1136/gut.41.6.832
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of procalcitonin and interleukin 8 in the prediction of infected necrosis in acute pancreatitis

Abstract: Background-Infection of pancreatic necrosis has a major impact on clinical course, management, and outcome in acute pancreatitis. Currently, guided fine needle aspiration is the only means for an early and accurate diagnosis of infected necrosis. Procalcitonin (PCT), a 116 amino acid propeptide of calcitonin, and interleukin 8 (IL-8), a strong neutrophil activating cytokine, are markers of severe inflammation and sepsis. Aims-To analyse the clinical value of PCT and IL-8 as biochemical parameters for predictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
150
3
11

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(170 citation statements)
references
References 23 publications
6
150
3
11
Order By: Relevance
“…Numerous studies have shown procalcitonin is elevated in cases of bacterial infection or sepsis and levels are considerably higher in bacterial infections than in viral infections [2,5,11,14,21,26,29,30,33]. Procalcitonin increases 2 to 4 hours after the onset of sepsis, which is later than proinflammatory cytokines, such as interleukin 6 (IL-6), but considerably earlier than CRP [31]. It reaches its peak after 6 hours and has a half-life of 25 to 30 hours [13,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown procalcitonin is elevated in cases of bacterial infection or sepsis and levels are considerably higher in bacterial infections than in viral infections [2,5,11,14,21,26,29,30,33]. Procalcitonin increases 2 to 4 hours after the onset of sepsis, which is later than proinflammatory cytokines, such as interleukin 6 (IL-6), but considerably earlier than CRP [31]. It reaches its peak after 6 hours and has a half-life of 25 to 30 hours [13,23].…”
Section: Introductionmentioning
confidence: 99%
“…It reaches its peak after 6 hours and has a half-life of 25 to 30 hours [13,23]. Some studies have shown the course of procalcitonin serum levels reflects the success of antibiotic treatment of bacterial infection rapidly, closely, and more reliably than CRP level [13,18,29,31,37].…”
Section: Introductionmentioning
confidence: 99%
“…Timely administration of adequate and effective antibiotic therapy is an important factor to solve those problems, and a thorough clinical examination and diagnostic workup is mandatory. Some reports showed that the administration of antibiotics alone had no effect on elevated PCT concentration 20 and simply administering antibiotics in the absence of an infection has no effect on CRP values, 21 suggesting that preoperative antibiotics might not direct influence on the PCT and CRP levels, however, it could have indirect effect on the PCT and CRP levels with presence or absence of infection or other relative condition. On the other hand, many previous studies demonstrated that PCT could be used to guide antibiotic therapy in patients with infection.…”
Section: Discussionmentioning
confidence: 99%
“…11 Rau et al noted a 19 fold increased risk of mortality among 230 patients with sterile necrosis, treated either operatively or conservatively, with multisystem >2 organ failure. 12 In addition to the presence of organ failure, the persistence of organ failure has been shown to a major determinant of mortality in acute pancreatitis. 13,14 In our study, admitted patients in the study group were assessed within 24hrs of presentation and BISAP score was calculated.…”
Section: Discussionmentioning
confidence: 99%